Detection of vibrio parahaemolyticus in raw vegetables from different wet markets in Kota Samarahan and Kuching, Sarawak - Ng, Lee Mei (Universiti Malaysia Sarawak, UNIMAS, 2010)
The increasing foodborne outbreaks caused by Vibrio parahaemolyticus had raised public concerns. Recently, raw vegetables have been claimed to be one of the reservoirs for V. parahaemolyticus. Therefore, it is important to determine the occurrence of V. parahaemolyticus in different raw vegetables. In this study, 3 different vegetables (leaf mustard, Kai-lan and lettuce) obtained from 3 different wet markets (Stutong, 3rd mile and 7th mile) were analysed for the presence of V. parahaemolyticus using direct PCR targeted on species specific gene, toxR gene and TCBS selective agar. The detection of tdh and trh virulence genes were also carried out to determine whether pathogenic V. parahaemolyticus was present in the vegetables samples. A total of 6 out of 63 vegetables samples (9.5%) were detected positive for the presence of V. parahaemolyticus using direct PCR method. However, only 2 out of 6 V. parahaemolyticus isolates (33.3%) were detected to be positive for tdh gene but negative for trh gene. 20 out of 45 vegetables samples (44.4%) were detected to be positive for V. parahaemolyticus using selective agar, TCBS method. The detection of virulence genes among the vegetable samples analysed in this study suggested that there is a possibility of cross contamination of raw vegetables by V. parahaemolyticus. Hence, this would alert the public on the risk of foodborne illness infection brought by raw vegetables.